Kinematic and kinetic analysis to improve the overall fitness of wrestlers - Zohirov, K.; Berdiev, G.; Boykobilov, S.; Pardayeva, G.; Ochilov, M. (2024 4th International Conference on Technological Advancements in Computational Sciences (ICTACS), 2024)
Kinematic and kinetic analysis of gait parameters of professional athletes who are engaged in wrestling, are analyzed in this research. Walking is considered an important factor for a person in sports and everyday life. It is possible to reduce the risk of injury during training which is aimed at performing various technical methods and physical training exercises on the basis of analysis of gait parameters. Together with this, we should take into account that asymmetric features can also be found in athletes who are engaged in wrestling. In the study, significant differences in movement parameters and the causes of asymmetry in the gait parameters of wrestlers were studied. 15 professional wrestlers took part in the experiments, and their gait parameters were collected on the basis of the G-Sensor portable device and the Strength platform (BTS company). The data is collected based on the basis of tests which are specific in advance and are important in the sport of wrestling. Differences between the body movements were found in the response of the parameters of the gait phase to the ground reaction. A longer SwP was observed in the right leg, in the result it causes to decrease of SSP and forward movement of the right leg. In addition, it was observed that the ground reaction force was higher on the left side. This analyzes give more important information about the asymmetry of the body movements in wrestlers and the adaptation of training with prior knowledge of this condition reduces the risk of injuries. The gathered information is considered the important for adjusting the types and sessions of training, improving the general physical trainings of athletes.